Menguak Konsep Harga Dibalik Transaksi Ngaben Massal pada Komunitas Hindu - Ni Luh Ketut Sri Widiani; Ronald S. Badu; Nurharyati Panigoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to uncover the price concept behind mass cremation transactions in the Hindu community in West Toili District, Banggai Regency, Central Sulawesi Province. This research uses qualitative research methods using an ethnomethodological approach and values in Hindu religious teachings. Data collection was carried out through direct observation, interviews and documentation. Data analysis techniques in this research start from data reduction, data presentation, indexicality, reflexivity, and drawing conclusions. The research results found that the concept of mass cremation transaction prices involves several determining factors in determining the fees paid by collectors. These factors include the level of yadnya, the number of pilots, and the type of upakara/banten that the polluters receive. The costs incurred in mass cremation are not only material (cash), but also non-material including togetherness, responsibility and sincerity. This reflects the values ​​of togetherness, responsibility and spiritual respect in the implementation of Ngaben which is based on yadnya.